Overall survival nomogram and relapse-related factors of clear cell sarcoma of the kidney: A study based on published patients - Zhang, Yuan; Chu, Qian; Ma, Yue; Miao, Chunshu; Diao, Juan-juan (Frontiers in Pediatrics, 2022)
Background: Rarity limits the breadth of study on clear cell sarcoma of the kidney (CCSK). There is currently no predictive model that quantifies the overall survival (OS) of CCSK and a few large sample-based analysis of relapse-related factors. Methods: Patients were collected both from the Surveillance, Epidemiology, and End Results (SEER) database and case report articles extracted from global online document database to form 2 groups. The first was the OS group, which was used to build and verify the nomogram for predicting the OS of CCSK. Independent predictors of OS were screened by Cox regression analysis to develop the nomogram. Nomogram accuracy was assessed by C-index, receiver operating characteristic (ROC), calibration, and decision curve analysis (DCA) curves. In addition, the difference in OS between receiving radiotherapy or not in stage Ⅰ patients was analyzed by Chi-square test. The second was the relapse group, which was used to analyze the relapse-related factors by Cox regression analysis and Kaplan-Meier method with log-rank test. Result: 256 patients were included in the OS group. The stage, chemotherapy and radiotherapy were independent OS-related factors of CCSK, and the nomogram for predicting the OS of CCSK established based on them. The results of C-index, ROC, calibration and DCA curves showed that the nomogram has good discrimination, accuracy and clinical profitability. The Chi-squared test showed no significant difference in OS with receiving radiotherapy or not in stage I patients. Relapse group included 153 patients, of which 60 relapsed. The univariate Cox regression analysis showed no correlation between radiotherapy and relapse. The multivariate Cox regression analysis showed that stage and surgery/chemotherapy sequence were the independent factors for relapse. The log-rank test of 7 chemotherapeutic drugs showed that etoposide(E), cyclophosphamide(C), vincristine(V), and doxorubicin(D) (all P<0.05) had significant differences in preventing relapse, and then draw the relapse-free survival curves of these 4 drugs. Conclusion: Our nomogram can accurately quantify the OS of CCSK. There was no significant difference in OS between receiving radiotherapy or not in stage I patients. Stage, surgery/chemotherapy sequence, and the use of ECVD were relapse-related factors. Radiotherapy has no significant contribution to preventing relapse.